Tourists' Destination Loyalty through Emotional Solidarity with Residents: An Integrative Moderated Mediation Model. (March 2018) - Ribeiro, Manuel Alector; Woosnam, Kyle M.; Pinto, Patricia; Silva, João Albino
This study proposes a theoretical model integrating two lines of tourism research: emotional solidarity and destination loyalty. In order to test the proposed model, a survey of visitors to Cape Verde islands was undertaken. Structural equation modeling and moderated mediation analysis were implemented to assess the relationships involving visitors' emotional solidarity with residents, satisfaction, and destination loyalty. The three dimensions of emotional solidarity were considered in the study: feeling welcomed, sympathetic understanding, and emotional closeness. Results indicate that visitors' feeling welcomed and sympathetic understanding directly influence loyalty. In particular, the relationships involving visitors' feeling welcomed by residents, emotional closeness with residents, and sympathetic understanding with residents and loyalty were all mediated by satisfaction. Additionally, gender was found to moderate the conditional indirect effects of emotional closeness and feeling welcomed on loyalty (via satisfaction). Such relationships were stronger among male visitors. Implications as well as future research opportunities are offered.